Lipase and Laccase Encapsulated on Zeolite Imidazolate Framework: Enzyme Activity and Stability from Voltammetric Measurements. Issue 23 (8th November 2018) - Naseri, Maryam; Pitzalis, Federica; Carucci, Cristina; Medda, Luca; Fotouhi, Lida; Magner, Edmond; Salis, Andrea
Abstract: Abstract : Lipase ( Pseudomonas fluorescens ) and laccase ( Trametates versicolor ) were encapsulated on two zeolite imidazolate framework, ZIF‐8 and ZIF‐zni, materials using a one‐pot synthesis‐immobilization method in aqueous solution at room temperature. The synthesized immobilized biocatalysts (Lip@ZIF‐8, Lip@ZIF‐zni, Lac@ZIF‐8, and Lac@ZIF‐zni) were characterized by X‐ray diffraction, scanning electron microscopy, Fourier transform infrared spectroscopy, and thermogravimetric analysis. The enzymatic activities of the four immobilized biocatalysts were characterized via the electrochemical detection of the substrates, p‐nitrophenyl butyrate and 2, 2‐azinobis‐3‐ethylbenzthiazoline‐6‐sulfonic acid. For Lip@ZIF‐8 the specific activity was 91.9 U mg −1 and 123.1 U mg −1 for Lip@ZIF‐zni, while for Lac@ZIF‐8 and Lac@ZIF‐zni, the activity was 51 U mg −1 and 163 U mg −1, respectively, confirming that laccase retains a higher level of activity when immobilized onto ZIF‐zni than on ZIF‐8. Lac@ZIF‐8 was the most stable system on storage (15 days at 5 °C), retaining 94 % of initial activity, while Lip@ZIF‐zni biocatalyst had the optimal level of reusability, retaining 40 % of initial activity after five reaction cycles. Abstract : Look into the cage : Lipase and laccase were encapsulated in ZIF‐8 and ZIF‐zni metal organic framework materials using a one‐pot synthesis‐immobilization method in aqueous solution at room temperature. The synthesized enzyme@ZIF samples were characterized by XRD, FT‐IR, and TGA. Enzymatic activities and stabilities of enzyme@ZIF samples were determined through voltammetric methods.